Masculinities and Femicide - Messerschmidt, James W. (Qualitative Sociology Review, 2017)
The relationship between masculinity and femicide has been virtually ignored in the literature on both masculinities and femicide. The aim of this paper then is to concentrate on the relationship between masculinities and femicide by first briefly summarizing feminist theorizing in the 1970s and 1980s and its relation to the emergence of Raewyn Connell’s concept of “hegemonic masculinity.” Following that, new directions in scholarly work on hegemonic and non-hegemonic masculinities are discussed, with particular attention directed to the recent work of the author on the relationship among hegemonic, dominant, dominating, and positive masculinities. Finally, the paper concludes by briefly illustrating how this new conception of masculinities can be applied to two types of femicide: intimate partner femicide and so-called “honor” femicides.